2005
DOI: 10.4018/jwsr.2005010102
|View full text |Cite
|
Sign up to set email alerts
|

WSDL-Driven SOAP Compression

Abstract: A major drawback of using SOAP for application integration is its enormous demand for network bandwidth. Compared to classical approaches like Java­RMI and Corba, SOAP messages typically cause more than three times more network traffic. In this paper we will explore compression strategies and give a detailed survey and evaluation of state-of-the-art binary encoding techniques for SOAP. We also introduce a new experimental concept for SOAP compression based on differential encoding, which makes use of the commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 9 publications
0
45
0
Order By: Relevance
“…As the standard transport protocol between Web services, SOAP suffers from its significant consumption of network bandwidth [29]. This drawback derives from the fact that SOAP is built on the basis of XML.…”
Section: Challenges and Considerationsmentioning
confidence: 99%
“…As the standard transport protocol between Web services, SOAP suffers from its significant consumption of network bandwidth [29]. This drawback derives from the fact that SOAP is built on the basis of XML.…”
Section: Challenges and Considerationsmentioning
confidence: 99%
“…In addition, XML-based similarity and differential encoding can be exploited to enhance SOAP performance: comparing new SOAP messages to predefined WSDL grammars, processing only those parts of the messages which differ from the corresponding WSDL. Identifying the common parts of SOAP messages, and repeating the processing for only those parts which are different from the WSDL schema would avoid a large amount of unnecessary overhead, and thus allow reducing processing cost in SOAP parsing [89], serialization [2], de-serialization [1], and communications [91]. For more details, a comprehensive review on (XML) similarity-based SOAP performance enhancement techniques can be found in [88].…”
Section: Web Services Matching and Soap Processingmentioning
confidence: 99%
“…Furthermore, how to design test cases for a Web service using its limited information exposed remains a challenge. Meanwhile, how to mitigate the overhead caused by the Web services-specific transport protocols (e.g., SOAP) deserves further investigation [9].…”
Section: Introductionmentioning
confidence: 99%